2021
DOI: 10.3390/f12121691
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Urban Forest Landscape for Better Perceptions of Positive Emotions

Abstract: Interacting with urban spaces that are green and blue is believed to promote mental well-being and positive emotions. Therefore, there is an incentive to strategically design urban forest landscapes in a given space to evoke more positive emotion. In this study, we conducted a pilot study in Northeast China with 24 parks from 11 cities across 3 provinces. The subjects of the study are the visitors and a total of 1145 photos and selfies were collected from open micro-twitters in Sino Weibo (~50 individuals per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 43 publications
3
36
2
Order By: Relevance
“…On the other hand, it has been reported that coming across blue spaces in a wetland located in an urban forest park in temperate cities evoked sad emotions (Zhang et al, 2021). Furthermore, blue spaces in elevated wetlands induced more sadness in people (Zhang et al, 2021;Li et al, 2022a). However, these studies were undertaken in parks at the local level, and a study of perceived emotions in blue spaces among a larger regional distribution may be different from areas covered just by parks.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, it has been reported that coming across blue spaces in a wetland located in an urban forest park in temperate cities evoked sad emotions (Zhang et al, 2021). Furthermore, blue spaces in elevated wetlands induced more sadness in people (Zhang et al, 2021;Li et al, 2022a). However, these studies were undertaken in parks at the local level, and a study of perceived emotions in blue spaces among a larger regional distribution may be different from areas covered just by parks.…”
Section: Introductionmentioning
confidence: 99%
“…Urban blue space is a critical element of a city's environmental infrastructure, where wetlands account for a large proportion (Tuofu et al, 2021). People can perceive landscape metrics in a blue space as drivers to evoke positive emotions and post them online (Akpinar, 2016;Wei et al, 2019;Zhang et al, 2021;Li et al, 2022a,b;Yu et al, 2022) (Table 1). In coastal urban wetlands, it was reported that the proximity to a blue space was a key precondition to evoking positive self-affirmation in people (White et al, 2016;Freeman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations